2020
DOI: 10.1371/journal.pone.0232790
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional prevalence study of MERS-CoV in local and imported dromedary camels in Saudi Arabia, 2016-2018

Abstract: The Middle East Respiratory Syndrome-Coronavirus (MERS-CoV) is an endemic virus in dromedaries. Annually, Saudi Arabia imports thousands of camels from the Horn of Africa, yet the epidemiology of MERS-CoV in these animals is largely unknown. Here, MERS-CoV prevalence was compared in imported African camels and their local counterparts. A total of 1399 paired sera and nasal swabs were collected from camels between 2016 and 2018. Imported animals from Sudan (n = 829) and Djibouti (n = 328) were sampled on incomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…MERS-CoV genome sequences described by Chu et al revealed discrete regional patterns of genetic diversity in Africa [ 15 ], suggesting structured populations of MERS-CoV circulating in African camel herds. A recent study reported a high incidence of MERS-CoV RNA detected in camels from eastern Africa on import vessels destined for markets in Saudi Arabia, likely providing an opportunity for mixing between previously geographically isolated lineages [ 19 ]. Consistent with these observations, studies have shown extensive recombination between MERS-CoV lineages in the large camel markets of KSA and UAE [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…MERS-CoV genome sequences described by Chu et al revealed discrete regional patterns of genetic diversity in Africa [ 15 ], suggesting structured populations of MERS-CoV circulating in African camel herds. A recent study reported a high incidence of MERS-CoV RNA detected in camels from eastern Africa on import vessels destined for markets in Saudi Arabia, likely providing an opportunity for mixing between previously geographically isolated lineages [ 19 ]. Consistent with these observations, studies have shown extensive recombination between MERS-CoV lineages in the large camel markets of KSA and UAE [ 2 , 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the high prevalence of metabolic diseases -related pathophysiology in men [ 14 , 34 , 35 , 40 , 41 ] predisposes them to the expression of MERS-CoV disease. KSA has the 4 th largest camel to population ratio (1 to 40 persons) after Somalia, Mauritania (1 to 1.4) and Sudan (1 to 8.6) [ 39 , 48 ]. The prevalence of diabetes in these countries with high per-capita camel population (Mauritania 6.7%, Somalia 5.1%, Sudan 7.7%) is however substantially lower than that of Saudi Arabia and may not provide sufficient susceptible population to cause large outbreaks [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…KSA has the 4 th largest camel to population ratio (1 to 40 persons) after Somalia, Mauritania (1 to 1.4) and Sudan (1 to 8.6) [ 39 , 48 ]. The prevalence of diabetes in these countries with high per-capita camel population (Mauritania 6.7%, Somalia 5.1%, Sudan 7.7%) is however substantially lower than that of Saudi Arabia and may not provide sufficient susceptible population to cause large outbreaks [ 48 , 49 ]. The most recent seroprevalence of MERS-CoV among camels in Saudi Arabia was 92.7% and RNA detection rate was 17.2%, with some variation between imported and resident herds, but RNA detection was as high as 35.5% among resident camel herds than imported [ 11 , 29 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A longitudinal study in Egypt reported the virus spread to >90% of a herd within two months, followed by a rapid decline in antibodies following the end of the outbreak to suggest that multiple re-infections of herds can occur within a short period [18]. Younger camels are particularly susceptible to MERS-CoV infection when compared with older ones, shed more virus and could drive infections in camel herds [20]. The Horn of Africa, including Kenya, Sudan, Ethiopia, and Somalia, is home to over 70% of the global dromedary camels population, and camel movement from the region to the Arabian Peninsula exceeds 300000 animals every year through trade [21,22].…”
Section: Introductionmentioning
confidence: 99%